Performance optimization and kinetic analysis of HNO3 coupled with microwave rapidly modified coconut shell activated carbon for VOCs adsorption - Rong, Xing; Cao, Qing; Gao, Yan; Du, Xin; Dou, Huawei; Yan, Min; Li, Shijie; Wang, Qian; Zhang, Zhanchao; Chen, Baoming (Frontiers in Energy Research, 2023)
As a typical carbon-based material, activated carbon (AC) has satisfied adsorption performance and is of great significance in the field of volatile organic compounds (VOCs) pollutants removal. In order to further reveal the optimization mechanism of AC adsorption performance, coconut shell-based AC was selected as the research object, and different concentrations of HNO3 coupled with microwave were used for rapid modification and activation. The characteristic changes of pore structure and surface chemical of AC before and after rapid modification were analyzed, and the performance changes of VOCs absorption were discussed from the perspective of reaction kinetics. The pore structure and surface chemical properties of before and after modification were analyzed by X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Brunauer-Emmeta-Teller (BET) analysis, Fourier Transform Infrared Spectroscopy (FTIR), and Boehm titration. The results showed that HNO3 coupled with microwave could significantly eliminate impurities in the pores of AC. After impregnation in HNO3 at a concentration of 1.5 mol L−1 and under microwave irradiation of 900 W, the number of micropore on the surface of samples increased slightly. When the impregnation concentration of HNO3 continued to increase, the two adjacent pore structures of the samples merged, which lead to a large decrease in the number of micropore and a corresponding increase in the proportion of mesoporous. Meanwhile, the specific surface area SBET of the modified NAC-6 sample increased to 1,140.40 m2 g−1, and the total acidic oxygen-containing functional groups on the surface increased by 0.459 mmol g−1 compared to that of the unmodified raw carbon. Furthermore, by analyzing the experimental results of formaldehyde adsorption on AC samples, it was concluded that the saturated adsorption capacity of the modified NAC-6 sample was 43% higher than that of the raw carbon. This study provides a more convenient and faster modification method for AC in the field of gas phase pollutants purification, which is helpful to realize the practical engineering application of AC with high efficiency, energy saving and sustainable.